Impact of age on transcatheter aortic valve implantation outcomes: a comparison of patients aged ≤ 80 years versus patients > 80 years - van der Kley, Frank (J Geriatr Cardiol, 2016)
OBJECTIVE: To investigate the procedural outcomes and the long-term survival of patients undergoing transcatheter aortic valve implantation (TAVI) and compare study results of patients ≤ 80 years and patients > 80 years old. METHODS: A total of 240 patients treated with TAVI were divided into two groups according to age ≤ 80 years (n = 105; 43.8%) and > 80 years (n = 135; 56.2%). The baseline characteristics and the procedural outcomes were compared between these two groups of patients. RESULTS: With the exception of peripheral artery disease and hypercholesterolemia, which were more frequently observed in the older age group, baseline characteristics were comparable between groups. Complication rates did not differ significantly between patients ≤ 80 years and patients > 80 years. There were no differences in 30-day mortality rates between patients aged ≤ 80 years and patients > 80 years old (9.5% vs. 7.4%, respectively; P = 0.557). After a median follow-up of 28 months (interquartile range: 16–42 months), 50 (47.6%) patients aged ≤ 80 years died compared to 57 (42%) deaths in the group of patients > 80 years old (P = 0.404). CONCLUSION: The results of the present single center study showed that age did not significantly impact the outcomes of TAVI.